Kepemimpinan Transformasional Kepala Madrasah dalam Meningkatkan Mutu Madrasah (Studi Kasus di MA Matholi’ul Huda Bugel Jepara) - Subaidi Subaidi (Universitas Nurul Jadid Paiton Probolinggo, East Java, 2018)
This study describes the principal's transformational leadership in improving the quality of madrasas conducted at MA Matholi’ul Huda Bugel Jepara. This research is a qualitative research. Collecting data through observation, interviews, and document review. Data analysis in this study uses interactive models such as those developed by Miles and Huberman. The results of the study indicate that; first, the value of transformational leadership which includes four aspects, namely: Idealized Influence or Inspirational Motivation, Intellectual stimulation or intellectual stimulation, Individualized consideration or individual consideration; secondly, the leadership of the head of the madrasa Aliyah Matholi'ul Huda Bugel Jepara has built trust with teachers and employees, through a reliable example of the madrasa principals, the compatibility between what is said and done, the opportunity for teachers and employees to express opinions, give opportunity to take part in duties and responsibilities, also take part in various trainings; third, the quality of the MA Matholi'ul Huda Bugel Kedung Jepara with the title of